The Relation of Fault Fracture Density with the Residual Gravity; case study in Muria - Fajar Rizki Widiatmoko; Ratih Hardini Kusuma Putri; Huzaely Latief Sunan (Journal of Earth and Marine Technology (JEMT), 2021)
The usages of the FFD analytical method massively are utilized during the last decade, especially in the geothermal preliminary study that can show the prospect reservoir area. This article discusses the correlation of the FFD value with the residual gravity value that is assumed as an indication of the underneath magmatic body. The correlation of FFD value with residual gravity value is applied in Muria mountain. Muria is classified as the volcano body that contains the magmatic body, also exist Genuk volcano and Patiayam hill around Muria. The correlation shows that FFD value and residual gravity value have a relation, but especially for the uninfluenced by structural activity has a low value of FFD. The correlation of FFD and residual gravity is double-checked with the ground truth data, it showing the proof relation. This way of methodology may use for finding the underneath magmatic body, especially applied to the surface that has not been influenced by structural activity.